2016
DOI: 10.1007/s10461-015-1284-7
|View full text |Cite
|
Sign up to set email alerts
|

How Different are Men Who Do Not Know Their HIV Status from Those Who Do? Results from an U.S. Online Study of Gay and Bisexual Men

Abstract: We compared self-described HIV-positive (31.6 %, n = 445), HIV-negative (56.8 %, n = 801), and HIV-unknown (11.6 %, n = 164) gay and bisexual men on sociodemographic and behavioral characteristics. Participants from across the U.S. were enrolled via a popular sexual networking website to complete an online survey. In total, 44.8 % of HIV-negative and HIV-unknown men said they had not been tested for HIV in the CDC-recommended last 6 months. HIV-unknown men significantly differed from HIV-negative and HIV-posit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
11
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 43 publications
1
11
1
Order By: Relevance
“…The CDC recommends that sexually active MSM should be tested annually, and clinicians should consider the potential benefits of more frequent HIV screening (eg, every three or six months) for some asymptomatic sexually active MSM, based on their individual risk factors, local HIV epidemiology, and local policies [ 66 , 67 ]. Almost 15% of the sample (738/5065) had never performed an HIV test and 15% (762/5065) were only tested once in their lifetime, which is almost two-fold higher than that observed in a US study using a GSN app [ 68 ], but much lower than that found in other Brazilian studies [ 2 , 69 ]. Knowledge of HIV status enables individuals to make decisions about behavioral strategies to reduce HIV transmission risks, such as serosorting [ 70 - 72 ], using condoms with partners who do not share the same HIV status, or restricting behaviors to partners who are HIV-positive and have undetectable viral loads (UVLs) or HIV-negative partners that take PrEP [ 73 ].…”
Section: Discussionmentioning
confidence: 67%
“…The CDC recommends that sexually active MSM should be tested annually, and clinicians should consider the potential benefits of more frequent HIV screening (eg, every three or six months) for some asymptomatic sexually active MSM, based on their individual risk factors, local HIV epidemiology, and local policies [ 66 , 67 ]. Almost 15% of the sample (738/5065) had never performed an HIV test and 15% (762/5065) were only tested once in their lifetime, which is almost two-fold higher than that observed in a US study using a GSN app [ 68 ], but much lower than that found in other Brazilian studies [ 2 , 69 ]. Knowledge of HIV status enables individuals to make decisions about behavioral strategies to reduce HIV transmission risks, such as serosorting [ 70 - 72 ], using condoms with partners who do not share the same HIV status, or restricting behaviors to partners who are HIV-positive and have undetectable viral loads (UVLs) or HIV-negative partners that take PrEP [ 73 ].…”
Section: Discussionmentioning
confidence: 67%
“…Whereas “biomed sorting ” (a term that we do not believe has yet been used in the literature) more broadly describes individuals who seek out partners who are using a biomedical strategy, regardless of whether that strategy is PrEP or TasP (i.e., men on PrEP having sex with partners on PrEP or virally suppressed HIV-positive men, and vice versa). 48 In contrast to biomed matching, one can biomed sort without using a biomedical strategy themselves (i.e., someone not on PrEP seeking out partners who are on PrEP or using TasP). Unintended consequences of biomed matching/sorting include that men not using a biomedical strategy may be less likely to benefit from a partner’s use of the strategy—potentially further driving disparities in HIV infections.…”
Section: Introductionmentioning
confidence: 99%
“…These included racial and income disparities, housing instability, recent transactional sex, and perhaps most notably, recent methamphetamine use. 2 3 5 1315 Approximately four out of every 10 individuals in our study with HIV-positive results had recently used methamphetamine, compared with fewer than 1 in 10 among those with HIV-negative results. This finding highlights the ongoing need to address what has been termed the ‘double epidemic’ whereby methamphetamine use is integrally connected to risk for HIV.…”
Section: Discussionmentioning
confidence: 83%
“…In order to locate HIV testing where it is needed most, it is important to examine the ways in which someone at risk for HIV who has recently tested for HIV might differ from someone who has not. 5 The CDC recommends, minimally, annual HIV tests for GBM, though other guidelines have called for testing with greater frequency. 6 Clark et al 7 reported on data from more than 68 000 HIV tests conducted with GBM during the CDC’s Expanded HIV Testing Initiative.…”
Section: Introductionmentioning
confidence: 99%